PTH-008 Outcomes from an international multicentre hemospray registry. (8th June 2018) - Alzoubaidi, Durayd; Rusu, Radu; Dunn, Jason; Rey, Johannes W; Gulati, Shraddha; Hayee, Bu'Hussain; Dixon, Selena; Moreea, Sulleman; Napier, Duncan; Anderson, John; Dahan, Martin; Hu, Max; et al.
Abstract : Introduction: Acute gastrointestinal bleeding (AGIB) carries poor outcomes unless prompt endoscopic haemostasis is achieved. Hemospray is a novel intervention that creates a mechanical barrier over bleeding sites when applied endoscopically. Primary aim of this international prospective multicentre registry is to collect outcomes of patients with AGIB after endoscopic Hemospary application. Secondary outcomes of rebleeding, disease and procedure specific outcomes are also collected. Method: Prospective data (Jan2016-Jan2018) from 11 centres across UK, France and Germany collected. Hemospray used as mono therapy, dual-therapy with standard haemostatic techniques or rescue therapy once standard methods failed. Immediate haemostasis defined as cessation of bleeding within 5 min after application of Hemospray. Rebleeding defined as subsequent drop in Hb (>2 g/L), haematemesis, persistent melaena with haemodynamic compromise post therapy. Results: 275 cases recruited worldwide(203 M and 72 F). Median pretreatment Blatchford score (BS) 11 for all cases. 246 patients (89%) achieved immediate haemostasis after endoscopic therapy with Hemospray (table 1). Similar haemostasis rates noted in the Hemospray monotherapy (92 % ), combination therapy (90 % ) and rescue therapy (85 % ) group. Peptic ulcer bleed was the most common pathology (53%) and forrest Ib the most common lesion type (66%). 29 patients did not achieve immediate haemostasis.Median BS was higher in this group at 13 (IQR 11–16, p<0.05). Forrest Ib was the most common lesion type in this group (76%, p<0.05). 28 cases of rebleeding reported after successful haemostasis. The median BS in these was higher at 13 (IQR 10.25–14.75, p<0.05). Forrest Ib was the most common bleed in this group (50%, p<0.05). Conclusion: These data show high rates of immediate haemostasis (89%). Forrest Type 1b lesions have a higher rate of unsuccessful haemostais and increased risk of rebleeding after therapy. Patients with rebleeding and unsuccessful treatment had higher BS at baseline. The expansion of this international registry will provide data on the efficacy of Hemospray in various disease and patient types over the coming years.